2015
DOI: 10.3109/14767058.2015.1094794
|View full text |Cite
|
Sign up to set email alerts
|

An elevated amniotic fluid prostaglandin Fconcentration is associated with intra-amniotic inflammation/infection, and clinical and histologic chorioamnionitis, as well as impending preterm delivery in patients with preterm labor and intact membranes

Abstract: Objective To determine whether an elevated amniotic fluid concentration of prostaglandin F2α (PGF2α) is associated with intra-amniotic inflammation/infection and adverse pregnancy outcomes in patients with preterm labor and intact membranes. Materials and Methods The retrospective cohort study included 132 patients who had a singleton pregnancy with preterm labor (<35 weeks of gestation) and intact membranes. Amniotic fluid was cultured for aerobic and anaerobic bacteria as well as genital mycoplasmas. Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 214 publications
0
26
0
Order By: Relevance
“…Interestingly, in all of the cases, Ureaplasma urealyticum was found in the amniotic cavity by conventional microbiological techniques or live/dead staining. This genital mycoplasma was either found to be alone or associated with Mycoplasma hominis , both of which are associated with spontaneous preterm labor and birth 32, 62, 63, 78, 79, 99-104 and/or clinical chorioamnionitis 73, 104 , both regarded as major clinical pregnancy complications 105-115 . Genital mycoplasmas can induce severe inflammatory responses in the amniotic cavity and surrounding tissues 116-120 , which may be characterized by the migration of maternal neutrophils into this compartment, as demonstrated herein.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in all of the cases, Ureaplasma urealyticum was found in the amniotic cavity by conventional microbiological techniques or live/dead staining. This genital mycoplasma was either found to be alone or associated with Mycoplasma hominis , both of which are associated with spontaneous preterm labor and birth 32, 62, 63, 78, 79, 99-104 and/or clinical chorioamnionitis 73, 104 , both regarded as major clinical pregnancy complications 105-115 . Genital mycoplasmas can induce severe inflammatory responses in the amniotic cavity and surrounding tissues 116-120 , which may be characterized by the migration of maternal neutrophils into this compartment, as demonstrated herein.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cytokines and chemokines stimulate PG production (63,64) and neutrophil infiltration and the release of MMPs (65), thus leading to cervical ripening and weakening/rupture of the fetal membranes. Indeed, the levels of MMPs (66) and PGs (56,67) are significantly increased within the amniotic fluid and fetal membranes during chorioamnionitis.…”
Section: Figmentioning
confidence: 99%
“…The intra-amniotic inflammatory response is characterized by an increased amniotic fluid white blood cell count [3337] and increased concentrations of inflammatory mediators, such as cytokines [27, 3436, 3875] and prostaglandins [7685]. However, there is a paucity of information about the cellular composition of the intra-amniotic inflammatory response in clinical chorioamnionitis, and most studies have reported changes in the total white blood cell count of the amniotic fluid while using a hemocytometer chamber (e.g.…”
Section: Introductionmentioning
confidence: 99%